Clinical Study to Assess the Efficacy and Safety of a Citrus Polyphenolic Extract of Red Orange, Grapefruit, and Orange (Sinetrol‐XPur) on Weight Management and Metabolic Parameters in Healthy Overweight Individuals. (3rd April 2013) - Dallas, Constantin; Gerbi, Alain; Elbez, Yves; Caillard, Philippe; Zamaria, Nicolas; Cloarec, Maurice
<x xml:space="preserve">Abstract</x> The present study investigated the efficacy and safety effects of Sinetrol‐XPur (polyphenolic citrus dry extract) in weight management; metabolic parameters; and inflammatory, glycemic and oxidative status. In a 12‐week, randomized, double‐blind, placebo‐controlled trial, Sinetrol‐XPur was given to overweight subjects twice daily with meals in the tested group (N = 47) versus a placebo group (N = 48). Waist and hip circumference and abdominal fat were decreased in the Sinetrol‐XPur group as compared with the placebo group (p < 0.0001) (−5.71% vs −1.56% for waist, −4.71% vs −1.35% for hip and −9.73% vs −3.18% for fat). Inflammatory markers were reduced (C‐reactive protein: −22.87% vs +61%; fibrinogen: −19.93% vs −1.61%, p < 0.01). Oxidative stress was lowered as seen by the reduction of malondialdehyde (−14.03% vs 2.76%) and the increase in superoxide dismutase and glutathione (17.38% vs 2.19% and 4.63% vs −2.36%, respectively, p < 0.01). No adverse effects were observed. Kidney, liver, and lipid panels remained unchanged. These results indicated that Sinetrol‐XPur supplementation is a viable option for reducing abdominal fat, waist and hip circumference, and body weight and for improving inflammatory, glycemic, and oxidative status in healthy overweight individuals. Copyright © 2013 John Wiley & Sons, Ltd.